EUS-guided interventional therapies for pancreatic diseases - Xu, Rongmin; Zhang, Kai; Ge, Nan; Sun, Siyu (Frontiers in Medicine, 2024)
Endoscopic ultrasound (EUS) is an integrated diagnostic technique merging endoscope and ultrasound to examine the digestive system. EUS has emerged as a primary diagnostic method for pancreatic diseases due to its distinctive benefits. Over the past four decades, EUS has undergone a transformation, shifting its role from primarily diagnostic to increasingly therapeutic. Additionally, in recent years, EUS has emerged as an increasingly prominent adjunctive or alternative approach to conventional surgical interventions. This review provides a comprehensive analysis of current technological approaches in the treatment of pancreatic diseases. The dynamic interplay with diverse therapeutic approaches has reinvigorated EUS and shaped its trajectory in the management of pancreatic diseases.